Comprehensive investigation of postmortem glucose levels in blood and body fluids with regard to the cause of death in forensic autopsy cases. Issue 6 (November 2015) - Chen, Jian-Hua; Michiue, Tomomi; Inamori-Kawamoto, Osamu; Ikeda, Sayuko; Ishikawa, Takaki; Maeda, Hitoshi
Highlights: Fatal insults induce hyperglycemia involved in stress responses. This study investigated postmortem glucose levels in blood and body fluids. Glucose levels were higher in diabetic cases, showing site-to-site correlations. Stress-induced hyperglycemia was evident in acute death of non-diabetic subjects. Characteristic findings were also detected in alcohol abuse and thermal disorders. Abstract: The serum glucose level is regulated within a narrow range by multiple factors under physiological conditions, but is greatly modified in the death process and after death. The present study comprehensively investigated glucose levels in blood and body fluids, including pericardial fluid (PCF), cerebrospinal fluid (CSF) and vitreous humor, reviewing forensic autopsy cases ( n  = 672). Right heart blood glucose level was often higher than at other sites, and the CSF glucose level was the lowest, showing greater dissociation in acute/subacute death cases. The glucose level was higher in the diabetic (high HbA1c) than in the non-diabetic (low HbA1c) group at each site ( p  < 0.01–0.0001). Fatal diabetic ketoacidosis cases had evidently high glucose levels at each site; whereas in the non-diabetic group, blood glucose level was higher in fatal alcohol abuse, saltwater drowning, electrocution, cerebrovascular disease and sudden cardiac death due to ischemic heart disease. Fatal methamphetamine (MA) abuse, sepsis, malnutrition (starvation) and hypoglycemia due to antidiabetics showed markedly lower blood glucose levels. Ketones in bilateral cardiac blood and PCF were increased in diabetic ketoacidosis and fatal alcohol abuse as well as in most cases of hyperthermia (heatstroke), hypothermia (cold exposure) and malnutrition. These findings suggest that combined analysis of glucose, HbA1c and ketones in blood and body fluids is useful to investigate not only fatal diabetic metabolic disorders but also death processes due to other causes, including alcohol and MA abuse, as well as thermal disorders, sepsis and malnutrition.